Responses of corn root protoplasts to exogenous reduced nicotinamide adenine dinucleotide: Oxygen consumption, ion uptake, and membrane potential - Lin, Willy (1982)
Addition of 1.5 mM NADH tripled the O(2) consumption in corn root protoplasts. The stimulation was temperature and pH dependent, specific to NADH, and accompanied by a 2- to 3-fold increase in K(+) and P(i) uptake into protoplasts. The increase in ion uptake was not due to the accumulation of NADH into protoplasts. The effect of exogenous NADH on O(2) consumption and ion uptake was also evident in corn root segments but to a lesser extent. A 20-mV hyperpolarization of protoplast membrane potential occurred on addition of NADH and was abolished by the uncoupler carbonyl cyanide p-trifluoromethoxyphenylhydrazone. Increases in cell volume of 30% and 40% were detected in response to NADH/H(+) and NADH/H(+)/K(+), respectively. The data are discussed in terms of a transmembrane redox reaction and the possibility that some part of the energy-linked ion transport may be driven by a NADH → O(2) electron-transport system in the plasmalemma.